Basin‐scale fluvial correlation and response to the Tethyan marine transgression: An example from the Triassic of central Spain. (27th April 2020) - Franzel, Maximilian; Jones, Stuart J.; Meadows, Neil; Allen, Mark B.; McCaffrey, Ken; Morgan, Tim
Abstract: The relationships between large‐scale depositional processes and the stratigraphic record of alluvial systems, e.g. the origin and distribution of channel stacking patterns, changing architecture and correlation of strata, are still relatively poorly understood, in contrast to marine systems. We present a study of the Castillian Branch of the Permo‐Triassic Central Iberian Basin, north‐eastern Spain, using chemostratigraphy and a detailed sedimentological analysis to correlate the synrift Triassic fluvial sandstones for ~80 km along the south‐eastern basin margin. This study investigates the effects of Middle Triassic (Ladinian) Tethyan marine transgression on fluvial facies and architecture. Chemostratigraphy identifies a major, single axially flowing fluvial system lasting from the Early to Middle Triassic (~10 Ma). The fluvial architecture comprises basal conglomerates, followed by amalgamated sandstones and topped by floodplain‐isolated single‐ or multi‐storey amalgamated sandstone complexes with a total thickness up to ~1 km. The Tethyan marine transgression advanced into the basin with a rate of 0.04–0.02 m/year, and is recorded by a transition from the fluvial succession to a series of maximum flooding surfaces characterised by marginal marine clastic sediments and sabkha evaporites. The continued, transgression led to widespread thick carbonate deposition infilling the basin and recording the final stage of synrift to early‐post‐rift deposition. We identify the nonmarine to marine transition characterised by significant changes in the Buntsandstein succession with a transition from a predominantly tectonic‐ to a climatically driven fluvial system. The results have important implications for the temporal and spatial prediction of fluvial architecture and their transition during a marine transgression. Abstract :